Haiti in the balance why foreign aid has failed and what we can do about it - Buss, Terry F. (Brookings Institution Press : National Academy of Public Administration, 2008)
"Tackles such questions as why has assistance been so ineffectual and what can be learned from Haiti's plight concerning foreign aid in general, by analyzing nearly twenty years of Haitian history, politics, and foreign relations"--Provided by publisher.